Analysis of factors influencing urban residents’ environmental protection behavior - He, Yu; Gu, Jintu (Frontiers in Psychology, 2025)
Against the backdrop of the “dual carbon” target becoming a national strategy, the environmentally friendly behavior of urban residents has become a key pivot to leverage ecological governance. However, in reality, although most urban residents identify with environmental protection concepts, they are constrained by multiple obstacles such as value conflicts, social norm pressures, economic cost considerations, and institutional contexts in daily practices such as garbage classification and low-carbon travel, forming deep bottlenecks that restrict the effectiveness of environmental governance. This study integrates the DEMATEL-ISM-MICMAC method to construct a three in one analytical framework of “driving mechanism transmission path governance strategy,” revealing the cascading impact chain from fundamental commitment to surface behavior, providing theoretical breakthroughs and practical paths for breaking the cognitive behavioral gap and achieving precise policy supply. The research results indicate that actual commitment (E8) serves as the fundamental driving force, with ultra-high driving force and extremely low dependence as the only independent factors, confirming that value internalization is the core engine of long-term environmental behavior; Environmental responsibility (E15) and civic behavior (E4) form a key hub node, with high centrality and strong interactivity linking the “cognition responsibility action” transformation chain; The surface level target ecological management (E1) exhibits significant passivity and is directly influenced by nine mid-level factors, highlighting the deep dependence of behavior implementation on systemic support. The dual low values of environmental emotion (E6) and verbal commitment (E7) expose their marginal position in the system, and pure emotional mobilization is difficult to activate the main behavioral chain. The four level transmission mechanism of E8 in the fundamental layer, E4/E15 in the middle layer, and E1/E16 in the surface layer further verifies that the improvement of environmental behavior efficiency needs to follow the progressive logic of “value foundation hub transmission terminal empowerment.” This study validates its practical effectiveness in promoting the transformation of residents from “cognitive identity” to “conscious action”, providing an operable and verifiable micro decision-making paradigm for the global urban carbon neutrality process, and promoting the paradigm shift of environmental governance research from factor identification to mechanism analysis and path optimization.